Pretty guardian Sailor Moon. 10 - Takeuchi, Naoko (New York : Kodansha Comics, 2013)
The threat of Dead Moon Circus is so great that the outer planet Guardians return to fight alongside their compatriots. But with Usagi now coughing up black blood as well, are they too late? And to make things worse, Queen Nehelenia's servant Zirconia casts another curse upon Usagi and Mamoru, sending them both back into childhood. However, Helios whisks away their spirits to Elysion, where they manage to break free and return to their true forms. After they rejoin their companions, the final showdown against Queen Nehelenia herself begins! Will the Sailor Guardians and Tuxedo Mask manage to save Earth and Elysion before the Queen transforms them into eternal realms of nightmares?"--Publisher's web site
Keywords: Fantasy comic books